IMPROVING LEARNING ACTIVITIES AND LEARNING OUTCOMES USING THE DISCOVERY LEARNING METHOD - Tri Adi Prasetya; Chrisna Tri Harjanto (VANOS Journal of Mechanical Engineering Education, 2020)
This research is action research conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. This research aims to improve the quality of the learning process. The Discovery learning method is used to improve the quality of learning. Stages of learning discovery methods consist of simulations, problem statements, data collection, verification, and generalization. Student learning activities are measured using an observation sheet. Student learning outcomes are measured using achievement tests in the form of multiple-choice questions. Data obtained in the study were analyzed using descriptive analysis. Data obtained from observations and achievement tests are used as a basis for improvement in the next cycle. The results of this study, discovery learning methods can improve learning activities and student learning outcomes. In the first cycle, students in the very active and active category were 63% and increased in the second cycle to 97%. In the first cycle, mastery learning reached 69% and increased in the second cycle to 87%.